The role of liver steatosis as measured with transient elastography and transaminases on hard clinical outcomes in patients with COVID-19. (May 2021) - Campos-Varela, Isabel; Villagrasa, Ares; Simon-Talero, Macarena; Riveiro-Barciela, Mar; Ventura-Cots, Meritxell; Aguilera-Castro, Lara; Alvarez-Lopez, Patricia; Nordahl, Emilie A; Anton, Adrian; Bañares, Juan; Barber, Claudia; Barreira-Diaz, Ana; et al.
Liver injury has been widely described in patients with Coronavirus disease 2019 (COVID-19). We aimed to study the effect of liver biochemistry alterations, previous liver disease, and the value of liver elastography on hard clinical outcomes in COVID-19 patients. We conducted a single-center prospective observational study in 370 consecutive patients admitted for polymerase chain reaction (PCR)-confirmed COVID-19 pneumonia. Clinical and laboratory data were collected at baseline and liver parameters and clinical events recorded during follow-up. Transient elastography [with Controlled Attenuation Parameter (CAP) measurements] was performed at admission in 98 patients. All patients were followed up until day 28 or death. The two main outcomes of the study were 28-day mortality and the occurrence of the composite endpoint intensive care unit (ICU) admission and/or death. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels were elevated at admission in 130 patients (35%) and 167 (45%) patients, respectively. Overall, 14.6% of patients presented the composite endpoint ICU and/or death. Neither ALT elevations, prior liver disease, liver stiffness nor liver steatosis (assessed with CAP) had any effect on outcomes. However, patients with abnormal baseline AST had a higher occurrence of the composite ICU/death (21% versus 9.5%, p  = 0.002). Patients ⩾65 years and with an AST level > 50 U/ml at admission had a significantly higher risk of ICU and/or death than those with AST ⩽ 50 U/ml (50% versus 13.3%, p  < 0.001). In conclusion, mild liver damage is prevalent in COVID-19 patients, but neither ALT elevation nor liver steatosis influenced hard clinical outcomes. Elevated baseline AST is a strong predictor of hard outcomes, especially in patients ⩾65 years.